USING GSM AUTHORIZATION FOR DISTANCE LEARNING SYSTEM (Journal of Information Technologies in Education (ITE), 2010)
In this article describes the structure of the expanded authorization program: an authorization program with feedback;As an feedback,the user is prompted to enter SMS message that was sent by program. In the article discribes the main stages of interaction with the GSM terminal.
Keywords: an authorization; expanded authorization; an authorization with feedback; main stages of interaction with the GSM terminal